Antigenic and genetic relationships among Rift Valley fever virus and other selected members of the genus Phlebovirus (Bunyaviridae) - Xu, Fangling; Liu, Dongying; Nunes, Marcio R T; DA Rosa, Amelia P A Travassos; Tesh, Robert B; Xiao, Shu-Yuan (The American journal of tropical medicine and hygiene, 2007)
Preliminary serologic data indicated that two South American phleboviruses (Belterra virus [BELTV] and Icoaraci virus [ICOV]) may be related to Rift Valley fever virus (RVFV), an African phlebovirus that causes severe hepatitis and hemorrhagic fever in humans. To further define this relationship and to investigate the underlying genetic basis, comparative serologic and genetic sequence analyses were performed with RVFV and five other New World phleboviruses (ICOV, BELTV, Salobo virus, Joa virus, and Frijoles virus). Serologically, a one-way cross reaction was confirmed between antibodies against these New World viruses and RVFV antigen. In contrast, phylogenetic analysis demonstrated clear separation of these viruses from RVFV, into distinct phylogenies, based on sequences of the small, medium, and large RNA segments.